The Effect of Occupational Safety and Health on Employee Performance Through Job Satisfaction During Covid-19 Pandemic - Muhsin Subair Darmadi; Rahman Kadir; Nuraeni Kadir; Alia Sri Wahyuni (Magister Management, Hasanuddin University, 2022)
This study aims to analyze the effect of occupational safety and health on employee performance through job satisfaction. The study collected data using questionnaires and then analyzed using path analysis. Before it, the stud applied some classical assumptions. The results showed that occupational safety and health had a positive and significant effect on job satisfaction. The same results are found for the relationship of occupational safety and health to employee performance. It is also found that job satisfaction has a positive and significant effect on employee performance. Occupational safety and health have a positive and significant indirect effect on employee performance when mediated by job satisfaction.